2019
DOI: 10.1097/md.0000000000014655
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lower respiratory tract infection in children with tracheobronchial foreign body aspiration

Abstract: The aim of this study was to determine the risk factors for lower respiratory tract infection (LRTI) in children caused by tracheobronchial foreign body aspiration (TFBA).A total of 351 patients were retrospectively reviewed; all patients were diagnosed with TFBA at West China Hospital of Sichuan University from 2015 to 2017. Univariate analyses and multivariate analysis were used.Age (<2 years) (P < .001), type of foreign body (plant) (P < .001), shape of foreign body (nonsmooth) (P < .001), and residence tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 32 publications
2
32
1
5
Order By: Relevance
“…For anatomic reasons, the foreign body most often locates in right main bronchi. The right bronchi is an extension of the trachea, it runs more vertically, it is wider and shorter compared to the left bronchi [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For anatomic reasons, the foreign body most often locates in right main bronchi. The right bronchi is an extension of the trachea, it runs more vertically, it is wider and shorter compared to the left bronchi [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that thoracic computed tomography (CT) has higher specificity and sensitivity than chest X-ray in the diagnosis of FBA [6,10]. CT may allow for a more accurate assessment of the location of the foreign body, determine to what extent the foreign body obstructs the airway, and may identify related complications [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LRTI is defined as infection and inflammation of trachea, main bronchus and lung bronchi. Imaging basis includes preoperative cervicothoracic CT and intraoperative rigid bronchoscopy 10 . Clinical diagnosis is based on relevant clinical guidelines 11,12 .…”
Section: Collection Of Clinical Datamentioning
confidence: 99%
“…According to previous studies, there was no correlation between the type of TFBA and LRTI in animal studies, whereas the retention time of TFBA was related 9 . A research reported that type, shape and the retention time of TFBA and age were associated with LRTI 10 . Therefore, we retrospectively analyzed the children who were applied TFBA extraction in our hospital in order to determine the occurrence of LRTI and analyze its risk factors.…”
Section: Introductionmentioning
confidence: 99%